Undermining, defusing or defending European integration? Assessing public communication of European executives in times of EU politicisation - Bart Joachim Bes; Martijn Schoonvelde; Christian Rauh (European Journal of Political Research, 2020)
How do mainstream political executives cue their politicised constituencies on European integration? Moving beyond static expectations that EU politicisation induces executives to either undermine, defuse or defend integration, this article theorises executives' incentives under different configurations of public and partisan Euroscepticism in their home countries. Expectations are tested on the sentiment and complexity that executives attach to European integration in almost 9,000 public speeches delivered throughout the Euro Crisis. It is found that national leaders faced with sceptical public opinion and low levels of partisan Euroscepticism rhetorically undermine integration, whereas European Commissioners faced with similar conditions are prone to defend it. These responses intensify disproportionally with growing public Euroscepticism, but are moderated by Eurosceptic party strength in surprising ways. When such challenger parties come closer to absorbing the Eurosceptic potential in public opinion, executive communication turns more positive again but also involves less clear rhetorical signals. These findings move beyond existing uniform expectations on mainstream responses to Eurosceptic challenges and highlight the relevance of different domestic configurations of EU politicisation.
doi:10.7910/DVN/NDJY0J
Keywords: 330; politicisation; European integration; elite communication; sentiment analysis; text complexity